Human monocyte response to Andean-native starch nanoparticles - Gatto, Francesca (2016)
We used starches from two different Andean-native tubers to prepare nano-sized particles, and tested their ability to stimulate inflammatory reactions in human monocytes. Our data show that the release of inflammatory cytokines by monocytes can be differentially modulated by the administration of non-toxic doses of nanoparticles synthesized from the starch of the Andean sub-species Solanum tuberosum and Solanum goniocalyx. Furthermore, we observed a starch-nanoparticle-specific increase in inflammatory chemokine-dependent migration, and an up-regulation of immunoglobulin receptor CD16. Based on this preliminary study, we conclude that different potato starch nanoparticles possess specific properties that can induce immune responses and may be employed as immune modulators in the future.